The Role of Religious Leaders in Instilling Religious Moderation in the Millennial Generation: Study on Millennial Generation in Borong Kapala, Bantaeng - Siti Hardianti (Jurnal Indonesia Studi Moderasi Beragama, 2024)
The purpose of this study was to determine the role of religious leaders in instilling an attitude of religious moderation in the millennial generation in Borong Kapala, Kab. Bantaeng. This research method uses the type of field research. This research was conducted in 2021. Data collection methods through data research using observation, interviews, and documentation. Data analysis was carried out through three stages, namely (1) data reduction; (2) data exposure; and (3) conclusion drawing. The results revealed that the purpose and urgency of religious moderation is to create balance, peace, and prosperity. Because every religion or understanding teaches good values and upholds humanity, religious moderation is very important because the tendency to practice religious teachings is sometimes excessive and often leaves one-sided truth and considers itself the most correct while others are wrong. So, we need to know that the purpose of religious moderation is to create a society always at peace without having to look at each other.